Online monitoring of PVT SiC bulk crystal growth using digital x-ray imaging - Wellmann, Peter; Bickermann, Matthias; Grau, M.; Hofmann, Heinz-Dieter; Straubinger, Thomas; Winnacker, Albrecht (Materials Research Society Symposium - Proceedings, 1999)
An advanced method based on x-ray imaging is presented which allows us to visualize the ongoing processes during physical vapor transport (PVT) growth of SiC. Using a high resolution and high speed x-ray imaging detector based on image plates and digital recording we are able to follow the SiC bulk single crystal growth as well as the evolution of the SiC powder source inside the inductively heated graphite crucible on-line and quasi-continuously.